2008
DOI: 10.1002/anie.200802472
|View full text |Cite
|
Sign up to set email alerts
|

Stereoretentive Halogenations and Azidations with Titanium(IV) Enabled by Chelating Leaving Groups

Abstract: Titanium does it again! With the help of nucleophile‐assisting leaving groups (NALGs), alkyl bromides, iodides, and, for the first time, azides are obtained from sulfonates with complete retention of configuration. Critical to the design of these new titanium(IV) reactions has been the use of NALGs which are thought to chelate the Lewis acid reagent in the transition state promoting an SNi‐type mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…The initial inclination to use titanium(IV) fluoride in reactions with chelating leaving groups was based on our desire to develop a stereoretentive fluorination reaction as a follow-up to our success with chlorinations [14] and brominations [9] using the corresponding Ti(IV) halogen reagents. Although currently under study by various groups for use in dental varnishes, [15] titanium(IV) fluoride has received only modest attention from the organic synthesis community [16] probably due to its moderate complexing ability, [17] propensity for oligomer complex formation, and sparing solubility in typical reaction solvents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial inclination to use titanium(IV) fluoride in reactions with chelating leaving groups was based on our desire to develop a stereoretentive fluorination reaction as a follow-up to our success with chlorinations [14] and brominations [9] using the corresponding Ti(IV) halogen reagents. Although currently under study by various groups for use in dental varnishes, [15] titanium(IV) fluoride has received only modest attention from the organic synthesis community [16] probably due to its moderate complexing ability, [17] propensity for oligomer complex formation, and sparing solubility in typical reaction solvents.…”
Section: Resultsmentioning
confidence: 99%
“…[24] Finally, primary alcohols (table 3, entry 11) reacted very slowly, consistent with our previous work with titanium(IV) mediated reactions. [9] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that radiofluorination at aliphatic carbon 7 and silicon 8 can be accomplished using metal chelating leaving groups capable of facilitating nucleophilic substitution reactions. We dubbed such groups as “nucleophile assisting leaving groups” (NALGs), arguing that the observed rate enhancements afforded by these nucleofuges are primarily due to stabilizing interactions between substrates and metal-nucleophile pairs to lower transition state energies.…”
Section: Introductionmentioning
confidence: 99%